Peran Kepuasan Kerja Dalam Memediasi Pengaruh Stres Kerja Dan Kepemimpinan Terhadap Komitmen Organisasi Di Toko Baru Bumiayu - Nur Fauziah , Hana; Susanto , Adi; Maulida Berniz , Yulis (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2024)
This study aims to analyze the effect of job satisfaction in mediating job stress and leadership, on organizational commitment at Toko Baru Bumiayu. This research was conducted on the employees of Toko Baru Bumiayu. The data used in this study is primary data obtained by distributing questionnaires to the respondents. The sample in this study were 114 respondents. The sampling technique used probability sampling with random sampling method. Data analysis in this study used multiple linear regression analysis with the help of SPSS V.20. Based on the results of this study, it shows that job stress has a negative and significant effect on organizational commitment, leadership has a positive and significant effect on organizational commitment, job stress has a negative and significant effect on job satisfaction, leadership has a positive and significant effect on job satisfaction, job satisfaction is unable to mediate job stress on organizational commitment, and Job satisfaction can mediate leadership on organizational commitment at Toko Baru Bumiayu.